Psychological capital and entrepreneurial success: the mediating role of entrepreneurial bricolage among Ugandan microentrepreneurs - David. Iga; Samuel Ssekajja Mayanja; Jotham M. Byarugaba (Cogent Business & Management)
This study explores the mediating role of entrepreneurial bricolage in the relationship between psychological capital and entrepreneurial success among microentrepreneurs in Kampala, Uganda. A cross-sectional survey design and quantitative approach were employed to collect data from 353 and analyzed through SPSS 23 and AMOS. The findings indicate that entrepreneurial bricolage plays a partial mediating role in the relationship between psychological capital and entrepreneurial success. In otherwords, entrepreneurial bricolage is a conduit through which psychological capital connects to entrepreneurial success. The study specifically focused on Kampala district, as it has the largest concentration of microentrepreneurs, meaning the results may not be generalized to the entire country. The study highlights that microentrepreneurs who cultivate and refine their mental skills, while strategically harnessing both internal resources, such as personal experiences, and external resources, like networks, are more likely to attain business success. This research contributes to entrepreneurship literature by highlighting the dual role of psychological capital and resourcefulness in promoting microenterprise success in resource-constrained environments. Additionally, the study emphasizes the role of psychological capital in shaping microentrepreneurs' decisions on how to creatively combine limited resources to achieve both business and personal goals, drawing on the principles of Entrepreneurial Bricolage theory.